The impact of excitotoxic blockade on the evolution of injury following combined mechanical and hypoxic insults in primary rat neuronal culture - Todd F. Glass; Brandi Reeves; Frank R. Sharp (Neurobiology of Disease, 2004)
Traumatic brain injury (TBI) involves alterations in neuronal physiology, often complicated by secondary hypoxic or hypotensive events. Excitotoxicity is an important process induced in both TBI and hypoxic or ischemic insults to the brain. We investigated two hypotheses: (1) excitotoxicity is more prominent following combined mechanical and hypoxic injury than either alone; (2) both AMPA and NMDA receptor activation mediate combined mechanical and hypoxic injury. Media in primary mixed neuronal cultures were replaced with conditioned media containing MK801 (NMDA antagonist) and/or NBQX (AMPA/kainate antagonist). Cultures were then subjected to mechanical injury. Afterward, media were exchanged for hypoxic media containing the antagonist, and plates were placed in hypoxia chambers for 7 h. At 24 h following hypoxia, LDH release, trypan blue uptake, and morphologic changes were assessed. Blockade had no effect after mechanical injury. After hypoxia, MK801 and combined MK801/NBQX decreased LDH and trypan blue to control levels. NBQX alone after hypoxia had less impact. After combined mechanical injury and hypoxia, both MK801 and NBQX partially reduced LDH and trypan blue. Combining the antagonists led to reduction to control values for both endpoints. We conclude that excitotoxic processes are more prominent after combined than isolated injuries in neurons and that increased cell death is mediated by both NMDA and AMPA receptor activation following combined injuries.